Dampak Special 301 terhadap Industri Rekaman Indonesia - Hendra Tanu Atmadja (Jurnal Hukum IUS QUIA IUSTUM, 2003)
The United States'strong commitment to global protection of intellectual property rights is rooted in its goal to preserve or regain the competitiveness and dominance of United States exports. In recent years, the United States has been experiencing significant and growing trade imbalances with its trading partners. The development of the Section301 provisions in the Omnibus Trade and Competitiveness Act of 1988 ("Trade Act") over the past twenty years reflects the United States'commitment toward international intellectual property protection. Reacting to GATTs inability to ensureprompt action on complaintsfroth the United States involving proliferating bilateral and free trade agreements. Congress created Section 301 as part of the 1974 Trade Act Subsequently in 1984, recognizing the lack of intellectual property protection in other countries and the billions dollars lost by the United States intellectual property rights holders, Congress amended Section 301 to specifically address these issues. The 1984 Trade Act authorized the president to impose trade sanctions against any country that did not provide adequate intellectual property protection and engaged in "unreasonable and unjustifiable'' trade practices. The 1988Trade Act further amended Section 301 by creating Special 301 provisions, and by granting the United States Trade Representative ("USTR") authority to act on behalf of the interests of the United States intellectual property rights holders.